Effects of ultrasound on the taste components from aqueous extract of unsmoked bacon. (15th December 2021) - Zhang, Jian; Zhang, Wangang; Xing, Lujuan
Highlights: Ultrasound groups got higher sensory scores than non-ultrasonic group. Ultrasound can improve the taste characteristic of unsmoked bacon. Nine major metabolites are closely linked with taste improvement after ultrasound. Six metabolic pathways are tightly related to taste development after ultrasound. 1 H NMR-based metabolomics is an effective way to study taste profile. Abstract: To investigate the effects of ultrasound on the taste profile of unsmoked bacon, metabolite identification, metabolite analysis and metabolic pathway analysis were performed by 1 H NMR, multivariate statistical analyses and MetaboAnalyst respectively. Results showed that ultrasound improved the concentration of free amino acids and organic acids thus promoting the taste development of unsmoked bacon. Sensory results demonstrated that ultrasound groups (especially 500 W) had higher sensory scores compared with non-ultrasonic group, which could be attributed to the improved levels of nine metabolites (alanine, arginine, glutamate, isoleucine, lysine, tyrosine, valine, creatine and lactate) after ultrasound treatment. Meanwhile, six metabolic pathways (tyrosine metabolism, etc.) were screened as crucial pathways tightly related to the taste development of unsmoked bacon after ultrasound treatment. In conclusion, ultrasound is found to be an effective technology to improve the taste profile of unsmoked bacon.